The Relationship Between Strategic Roles and Performance: the Case of Multinational Corporations' Subsidiaries in Malaysia - Mustaffa, Zaidah (2003)
The general purpose of the study is to investigate the roles and strategic styles of multinational corporations' subsidiaries in Malaysia. Specifically, the study aims to explore the strategic roles of multinational subsidiaries with regards to local responsiveness and integration of activities, and the level of technological capability. The strategic roles are further related to subsidiaries' performance. In addition, the study also looks at the relationship between the dimensions of the strategic roles of multinational subsidiaries and performance, and with the business environment as the moderating variable. The methodology of the data collection is by a set of questionnaires sent out to multinational subsidiaries currently operating in Malaysia. Seventy-one (71) multinational corporations' subsidiaries participated in this study. Statistical analyses used for the study included cluster analysis, analysis of variance (ANOVA) and multiple regression.Data analyses revealed that there are five strategic roles of multinational subsidiaries with regards to local responsiveness of activities, integration of activities and technological capability. Industry characteristics, nationalities, age and foreign ownership stake of subsidiaries are found to be dependent on the strategic roles of subsidiaries. Subsidiary performance is found to be the same across strategic styles. The three dimensions of strategic roles, namely local responsiveness of activities, integration of activities and technological capability are found not to be related to performance but business environment does appear to act as a moderating variable between the three dimensions and performance. Results of the study present practical implications to policy makers, head office and subsidiary managers and local business players. The study also contributes to the body of knowledge in multinational subsidiaries participating in developing nations and in the area of international strategic management.